Telescope: an interactive tool for managing large-scale analysis from mobile devices. Issue 1 (23rd January 2020) - Brito, Jaqueline J; Mosqueiro, Thiago; Rotman, Jeremy; Xue, Victor; Chapski, Douglas J; la Hoz, Juan De; Matias, Paulo; Martin, Lana S; Zelikovsky, Alex; Pellegrini, Matteo; Mangul, Serghei
Abstract: Background: In today's world of big data, computational analysis has become a key driver of biomedical research. High-performance computational facilities are capable of processing considerable volumes of data, yet often lack an easy-to-use interface to guide the user in supervising and adjusting bioinformatics analysis via a tablet or smartphone. Results: To address this gap we proposed Telescope, a novel tool that interfaces with high-performance computational clusters to deliver an intuitive user interface for controlling and monitoring bioinformatics analyses in real-time. By leveraging last generation technology now ubiquitous to most researchers (such as smartphones), Telescope delivers a friendly user experience and manages conectivity and encryption under the hood. Conclusions: Telescope helps to mitigate the digital divide between wet and computational laboratories in contemporary biology. By delivering convenience and ease of use through a user experience not relying on expertise with computational clusters, Telescope can help researchers close the feedback loop between bioinformatics and experimental work with minimal impact on the performance of computational tools. Telescope is freely available at https://github.com/Mangul-Lab-USC/telescope .